Difficult discussions : issues and ideas for engaging college students in peace and justice topics - Finley, Laura L. (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
"Drawing from many disciplinary areas, this edited volume shares tools, techniques and ideas for engaging college students in difficult discussions. From sexual violence to race to poverty and more, chapters in the book present useful strategies as well as limitations in creating safe classroom spaces. Ideal for peace and justice educators, this volume also includes the voices of students in every chapter"-- Provided by publisher.
Keywords: Education, Higher -- United States.; College students -- United States.; Peace -- Study and teaching (Higher); Justice -- Study and teaching (Higher); Education -- Teaching -- Subjects -- Social Science.; Teaching of a specific subject.; Educational: Social sciences, social studies.; elektronické knihy; electronic books